Penerapan teknologi biopori dalam pencegahan banjir dan kekeringan yang sekaligus pembuatan biokompos di Kelurahan Delima Kecamatan Tampan Pekanbaru - Andi Dahliaty; Yuana Nurulita; Titania Tjandrawati Nugroho; Sri Helianty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Flooding is a problem that almost every year affects urban and rural areas. Generally, in urban areas, floods are caused more by the lack of smooth flow of water (sewage) due to waste dumped into the water stream and the reduction of water catchment areas. The Delima Subdistrict of Tampan Subdistrict has a simple housing area that has a limited home yard measuring around 7m x13m up to 10m x 15m per house unit. To meet clean water needs, this area uses bore wells which over time will reduce underground water reserves. The housing area is sometimes disemenised, which results in a lack of infiltration of rain water so that it is prone to flooding and drought. To overcome this, the community can apply biopore infiltration technology. This service activity aims to introduce biopore infiltration technology and invites the community to apply it and make biocompost from the infiltration hole. The method of service activities was carried out with material delivery techniques and discussions as well as demonstrations or practices in making biopori infiltration holes as an effort to overcome floods and droughts in settlements around the Delima Village, Tampan District, Pekanbaru. From the results of this activity it is known that the target community seemed enthusiastic about the material presented and there was an increase in the knowledge and insights of the participants about biopori absorption technology by around 80%.